The strange case of Dr Jekyll & Mr Hyde - Stevenson, Robert Louis (Edinburgh: Barrington Stoke, 2017)
A terrible killer lurks in London's dark and foggy corners. His crimes are witnessed, but no one can track him down. At the same time, the respectable Dr Jekyll is on a quest of his own. But Dr Jekyll's discoveries look set to unleash an appalling truth. Just how closely entwined is his identity with that of the brutish Mr Hyde? - Publishers description
Keywords: Horror tales